Immunostimulant Compounds Identification in Indonesian Underutilized Zingiberaceae Spices - Rosalina, Dian; Yuliana, Nancy Dewi; Anggraeni, Ririn; Prangdimurti, Endang (Molekul, 2023)
Spices are known for its health beneficial effect beside its function as flavouring and condiment. This study aimed to screen immunostimulant activities of 12 underutilized species of Zingiberaceae grown in Indonesia. The compound associated with immunostimulant activity in the most active sample was identified by linking the chromatogram profile of hexane, chloroform, ethyl acetate, methanol, and water fractions of the selected spices to its activity using orthogonal projection to the least square (OPLS) analysis, followed by LC-MS characterization. The result showed that Alpinia malaccensis and Zingiber ottensii had the highest lymphocyte cell proliferation index (SI) at concentrations of 400 ppm. A. malaccensis was chosen for the next step. The results of OPLS analysis showed that the retention time interval which strongly correlated with the immunostimulant activity was 27.0 – 28.5 minutes, which were abundant in methanol fraction. The mass spectra analysis of methanol fraction using UHPLC-HRMS showed that the respective retention time was attributed to flavokawain B. This compound was reported to increase rat splenocyte proliferation in vivo.